Unleash narrowband technologies for industrial Internet of Things services - Al-Rubaye, Saba; Rodriguez, Jonathan; Zanotti Fragonara, Luca; Theron, Paul; Tsourdos, Antonios (IEEE, 2019)
As the industrial market grows, it is becoming noticeable that there are many industrial Internet of things (IIoT) use cases for which existing technology cannot meet the huge demand of machine connectivity. For example, in the utility market, there is a strong trend to adopt new technology that can support positive business use case scenarios for efficient system operation and elaborate the dramatic increase of the services demands. Apart from this, most utility grid applications required long-range, low-power, secure, and reliable communications, which means narrowband (NB) technology can be the dominant choice. To address these challenges, this article provides a new framework architecture to enable technical decision makers to plan for NB-IIoT. Moreover, we highlight the key aspects of NB technology by focusing on the challenges, standardization, and requirements to facilitate the IIoT connectivity for industry revolutions. The motivation behind employing NB is to provide a high level of reliability, and better quality of service, and coverage. In particular, the article addresses the main applications of utility use cases under the NB umbrella, which can perform as a good bridge between utility services and the fundamental communication infrastructure. The utility use cases based on emerging technology can support the full array of smart grid services that are required for both central and distributed operation systems. Finally, the article provides connectivity solutions for potential IIoT deployment aiming to define a new roadmap for NB technology on specific industrial use cases.
Keywords: Smart grids; Narrowband; Reliability; Wireless communication; Business; Internet of Things